Parameter Scaling Effects on RLHF-Aligned Models in Legal Knowledge Benchmarking - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 8 peer-reviewed papers addressing the following research question: How does increasing parameter scale from 7B to 70B affect the accuracy of RLHF-aligned models on the Legal Knowledge level of the LawBench benchmark. 13 claims were extracted from source literature; 6 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 6.1/10. This report is a machine-generated literature synthesis and do
Machine-generated literature synthesis.